Helicopter emergency medical services demonstrate reduced time to emergency anaesthesia in an undifferentiated trauma population: a retrospective observational analysis across three major trauma networks - Daniel Heritage; Joanne Griggs; Jack Barrett; Scott Clarke; Rory Carroll; Richard Lyon; Duncan Bootland (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Early rapid sequence induction of anaesthesia (RSI) and tracheal intubation for patients with airway or ventilatory compromise following major trauma is recommended, with guidance suggesting a 45-min timeframe. Whilst on-scene RSI is recommended, the potential time benefit offered by Helicopter Emergency Medical Services (HEMS) has not been studied. We compared the time from 999/112 emergency call to delivery of RSI between patients intubated either in the Emergency Department or pre-hospital by HEMS. Methods A retrospective observational cohort study of major trauma patients in South-East England who received a pre-hospital RSI (PHRSI) or Emergency Department RSI (EDRSI) between 2 January 2018 and 24 September 2019. Data were extracted from the UK Trauma Audit and Research Network database. The primary outcome was the time from emergency call to delivery of RSI. Secondary outcomes included mortality at 30-days or hospital discharge, time from arrival of service at hospital or scene to RSI, time from emergency call to Computerised Tomography scan, and conveyance interval. Linear regression was used to model time to RSI in both groups. Results Of 378 eligible patients, 209 patients met inclusion criteria. 103 received a PHRSI and 106 received an EDRSI. Most patients were male (n = 171, 82%) and the median age was 48 years (IQR 28–65). 94% sustained a blunt injury mechanism and head was the most injured body region for both cohorts (n = 134, 64%). 63% (n = 67) of patients receiving a PHRSI were conveyed by helicopter. PHRSI was delivered significantly earlier with a median of 64 [IQR 51–75] minutes (95% CI, 60–68) compared with EDRSI with a median of 84 [IQR 68–113] minutes (95% CI, 76–94), p < 0.001). Conclusion Major trauma patients who had a pre-hospital RSI received this time-critical intervention sooner after their injury than those who received an emergency anaesthetic after conveyance to a specialist hospital. Patient outcome benefit of HEMS delivered early RSI should be explored.